Analysing the relationship between additive manufacturing market and GDP - Ficzere, Péter (Design of Machines and Structures, 2025)
This paper investigates the correlation between the additive manufacturing (AM) market and gross domestic product (GDP) in different regions around the world. Using data from Grand View Research (https://www.grandviewresearch.com) and the World Bank (https://data.worldbank.org), market trends, economic indicators and regional disparities were analysed. The study provides visualisations and tabular data to support the analysis, offering insights into the economic impact of AM technologies.